2018
DOI: 10.1111/jphp.13007
|View full text |Cite
|
Sign up to set email alerts
|

Tannins from Terminalia chebula fruits attenuates GABA antagonist-induced anxiety-like behaviour via modulation of neurotransmitters

Abstract: Terminalia chebula tannin-rich extract showed significant anxiolytic activity against picrotoxin and could be used as natural therapy in neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Additionally, the treatment of the same extract showed the significant anxiolytic activity against picrotoxin-induced anxiety model. 47 The present study indicated elevation of monoamine neurotransmitters by inhibition of brain MAO-A levels at the dose level of 200 mg/kg of the T.chebula extract treatment. This beneficial activity might be correlated with the presence of tannin rich compounds in T.chebula fruits.…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, the treatment of the same extract showed the significant anxiolytic activity against picrotoxin-induced anxiety model. 47 The present study indicated elevation of monoamine neurotransmitters by inhibition of brain MAO-A levels at the dose level of 200 mg/kg of the T.chebula extract treatment. This beneficial activity might be correlated with the presence of tannin rich compounds in T.chebula fruits.…”
Section: Discussionsupporting
confidence: 56%
“…In an animal study, Gupta et al reported that the hydroalcoholic extract of black myrobalan has anticonvulsant effects, enhances the effects of antiepileptic drugs, improves cognitive symptoms, and shows antioxidant effects (Kumar, Arora, Agarwal, & Gupta, 2018). In another animal study, Kumar et al demonstrated that the tannin‐rich extract of black myrobalan could neutralize picrotoxin's stressful effects by activating the GABAergic (gamma‐aminobutyric acid) pathway and could be used in the treatment of neurodegenerative diseases (Chandrasekhar, Phani Kumar, Navya, Ramya, & Anilakumar, 2018). These effects (related to Gupta et al and Kumar et al's studies) could aid in the negative and behavioral symptoms (excitement/ activity) of patients with schizophrenia by activating GABAergic mediated neurons (Shaw et al, 2020) and could also help explain the confusion observed in one of the patients due to possible interaction with the GABAergic or antiepileptic drugs that were being taken by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[26,28] Aqueous extract of Haritaki is found to have a good anxiolytic and antidepressant activity when evaluated against standard drug diazepam and imipramine respectively [29][30]. Tanin rich extract of Haritaki resulted in downregulation of serum cortisol level and maintained the level of 5HT and dopamine in the blood presenting anxiolytic activity [31]. Phytoconstituents found in Haritaki have a good therapeutic effect with no toxicity [32].…”
Section: Recent Researches and Evidence On Research Drugsmentioning
confidence: 99%